Impact of a university course on pre-service teachers' conceptions about environmental issues and environmental education - KONSTANTINOS J. KORFIATIS; TASOS HOVARDAS (Metaichmio Publications, 2008)
The paper presents the results of the evaluation of a university environmental course on pre-service teachers' conceptions of environmental issues and environmental education. The evaluation method leaned on the theory of social representations and used stimulus terms to trigger respondents' ideas. The course had a positive effect on participants' conceptions, as it was indicated by the transformation of the conceptual framework for the stimulus terms. Our findings offered valuable insights for the proper transformation of the course while the easiness of the applied method in data collection, renders feasible the longitudinal monitoring of course effects.